Withdrawal of life-support in paediatric intensive care - a study of time intervals between discussion, decision and death - Tibballs James; Oberender Felix (BMC, 2011)
Abstract Background Scant information exists about the time-course of events during withdrawal of life-sustaining treatment. We investigated the time required for end-of-life decisions, subsequent withdrawal of life-sustaining treatment and the time to death. Methods Prospective, observational study in the ICU of a tertiary paediatric hospital. Results Data on 38 cases of withdrawal of life-sustaining treatment were recorded over a 12-month period (75% of PICU deaths). The time from the first discussion between medical staff and parents of the subject of withdrawal of life-sustaining treatment to parents and medical staff making the decision varied widely from immediate to 457 hours (19 days) with a median time of 67.8 hours (2.8 days). Large variations were subsequently also observed from the time of decision to actual commencement of the process ranging from 30 minutes to 47.3 hrs (2 days) with a median requirement of 4.7 hours. Death was apparent to staff at a median time of 10 minutes following withdrawal of life support varying from immediate to a maximum of 6.4 hours. Twenty-one per cent of children died more than 1 hour after withdrawal of treatment. Medical confirmation of death occurred at 0 to 35 minutes thereafter with the physician having left the bedside during withdrawal in 18 cases (48%) to attend other patients or to allow privacy for the family. Conclusions Wide case-by-case variation in timeframes occurs at every step of the process of withdrawal of life-sustaining treatment until death. This knowledge may facilitate medical management, clinical leadership, guidance of parents and inform organ procurement after cardiac death.